ANALISIS PENERAPAN FILOSOFI THE TOYOTA WAY DALAM MANAJEMEN PUBLIC RELATIONS DI ERA DISRUPSI TEKNOLOGI - Sefy Andhriany; Tri Widyastuti; Danti Melani; Sefy Andhriany; Tri Widyastuti (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
Today, technology has developed very rapidly and is increasingly unpredictable, which makes companies develop strategies to stay alive in the midst of uncertainty. The study aims to analyze whether The Toyota Way will survive the era of disruption by adhering to fourteen management principles. The methodology used is a literature review with data collection on Toyota management elements, Public Relations management review, and previous research studies. The results show that the management elements Toyota has implemented will continue to be relevant by producing good inputs to stay afloat in the era of technological disruption.